2021
DOI: 10.37934/cfdl.13.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Combustion Process of Diesel and Ethanol Fuel in Reactivity Controlled Compression Ignition Engine

Abstract: Reactivity controlled compression ignition (RCCI) engine give advantages over conventional diesel engine with the promising engine power and good control on NOx and soot emission. The trend of the RCCI concept is still new and Is very important to control the ignition in order to control the combustion progress and emission. The objective of this study is to provide data on the combustion characteristics and emission of diesel as high reactive, and ethanol as the low reactive fuel in the RCCI engine. The engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…While the relation between the flow rate and the Nusselt number at temperature 45 °C is seen in Figure 2 at 0.7 percent nano particle concertation. In these two numbers, strong consensus can be seen [18,19]. The computation of the absolute average error shows 7 percent to be the water-based nanofluid prediction error.…”
Section: Validationmentioning
confidence: 94%
“…While the relation between the flow rate and the Nusselt number at temperature 45 °C is seen in Figure 2 at 0.7 percent nano particle concertation. In these two numbers, strong consensus can be seen [18,19]. The computation of the absolute average error shows 7 percent to be the water-based nanofluid prediction error.…”
Section: Validationmentioning
confidence: 94%
“…Meanwhile, Lee et al, [33] concluded that when the CO2 fraction changed from 0% to 50%, carbon monoxide (CO) and unburned hydrocarbons (UHC) emissions increased, while NOX emissions decreased. We can find more information about the subject of this study in previous papers [63][64][65][66].…”
Section: Model Validationmentioning
confidence: 99%
“…The objectives of the world are substituting fossil fuels by alternative fuels to reducing the pollutant emissions to meet the standard emissions regulations. It well known that the compression ignition (CI) engine produces high level of soot and NOX emissions that effect on both environment and health [1]. To confront technology, climate, and renewability challenges, different blends of fuels derived from a large variety of feedstock will be available in the future such as biodiesel-diesel blends and alcohol-diesel blends.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many studies have been documented on results of NOX and PM emitted from the oxygenated fuels combustion in diesel engines [7,8]. Zulkurnai et al, [9] stated that the NOX and soot decreased from combustion of ethanol-diesel blend which contribute in better engine performance and better environmental future. Most of studies reported that the soot emissions decreased as the percentage of biodiesel content increased in the fuel-blend [10].…”
Section: Introductionmentioning
confidence: 99%